Social impact bonds and the perils of aligned interests - Florentine Maier; Michael Meyer (Administrative Sciences, 2017)
Social impact bonds (SIBs) have been welcomed enthusiastically as a new funding tool for social innovation, yet also condemned as an instrument that neglects beneficiaries' and taxpayers' interests, opening profit opportunities in the field of social politics for smart private investors. We will shed a more analytical light on SIBs, assuming that, like any contract, SIBs try to align interests between partners with partly converging, partly diverging goals. Thus, it remains mainly a matter of negation, and non-profit social service providers as well as public agencies should avoid particular perils and pitfalls.
Keywords: 350; social impact bonds; financialization; commercialization